Barriers and Facilitators to the Implementation of Effective Alcohol Control Policies: A Scoping Review - Jankhotkaew J; Casswell S; Huckle T; Chaiyasong S; Phonsuk P (MDPI (Basel, Switzerland), 2022)
Implementation of effective alcohol control policies is a global priority. However, at the global and national levels, implementing effective policies is still challenging, as it requires commitment from multiple stakeholders. This review provides a synthesis of barriers and facilitators to implementing effective alcohol control policies. We conducted a scoping review from two main databases: Scopus and Web of Science, and the grey literature from the World Health Organization’s website. We included any studies investigating barriers and facilitators to implementing four effective policies: Alcohol pricing and taxation, control of physical availability, alcohol marketing control, and drink-driving policy. Articles published between 2000 and 2021 were included. The search yielded 11,651 articles, which were reduced to 21 after the assessment of eligibility criteria. We found five main barriers: resource constraint; legal loopholes; lack of evidence to support policy implementation, particularly local evidence; low priority of policy implementation among responsible agencies; and insufficient skills of implementers. Facilitators, which were scarce, included establishing monitoring systems and local evidence to support policy implementation and early engagement of implementing agencies and communities. We recommend that national governments pay more attention to potential barriers and facilitators while designing alcohol control regulations and implementing effective policies.
Copyright: © 2022 by the authors.
Keywords: barriers; effective alcohol policies; facilitators; policy implementation; Marketing; Public Policy